2022
DOI: 10.1108/maj-08-2019-2379
|View full text |Cite
|
Sign up to set email alerts
|

Effects of qualitative factors and auditors’ personal characteristics on materiality judgments

Abstract: Purpose The purpose of this paper is to investigate the effect of qualitative materiality factors on auditors’ assessment of materiality and the determination of the type of the auditors’ reports. This paper also analyzes whether differences in personal characteristics of auditors can influence their use of qualitative materiality factors in assessing material misstatements. Design/methodology/approach A questionnaire and experimental case studies were undertaken to determine whether differences in personal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…This means that the professional experience of the auditor has a significant impact on the relationship between GHGE assurance and the quality of the auditor's professional judgment on materiality, and therefore the null hypothesis is rejected and the alternative hypothesis H2 is accepted. This finding is consistent with the findings of several studies (e.g., DeZoort et al, 2019;Hegazy & Salama, 2022;DeZoort et al, 2023).…”
Section: The Results Of the Second Hypothesis Test (H2)supporting
confidence: 94%
See 4 more Smart Citations
“…This means that the professional experience of the auditor has a significant impact on the relationship between GHGE assurance and the quality of the auditor's professional judgment on materiality, and therefore the null hypothesis is rejected and the alternative hypothesis H2 is accepted. This finding is consistent with the findings of several studies (e.g., DeZoort et al, 2019;Hegazy & Salama, 2022;DeZoort et al, 2023).…”
Section: The Results Of the Second Hypothesis Test (H2)supporting
confidence: 94%
“…Regarding the impact of professional experience on the professional judgment of auditors regarding materiality, many previous studies (e.g., Bhattacharjee & Moreno, 2002;Asare et al, 2009;Martinov-Bennie & Pflugrath, 2009;Manita et al, 2011;Adam & Dacunha, 2019;DeZoort et al, 2019;Hegazy & Salama, 2022;DeZoort et al, 2023) have indicated that the quality of auditors' professional judgment regarding materiality varies based on their professional experience. These studies agreed on the positive and significant influence of auditors' professional experience on the quality of their professional judgment regarding materiality.…”
Section: Development Of H2mentioning
confidence: 99%
See 3 more Smart Citations